2016
DOI: 10.21037/hbsn.2015.11.03
|View full text |Cite
|
Sign up to set email alerts
|

High intensity focused ultrasound (HIFU) applied to hepato-bilio-pancreatic and the digestive system—current state of the art and future perspectives

Abstract: Background: High intensity focused ultrasound (HIFU) is emerging as a valid minimally-invasive imageguided treatment of malignancies. We aimed to review to current state of the art of HIFU therapy applied to the digestive system and discuss some promising avenues of the technology.Methods: Pertinent studies were identified through PubMed and Embase search engines using the following keywords, combined in different ways: HIFU, esophagus, stomach, liver, pancreas, gallbladder, colon, rectum, and cancer. Experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(29 citation statements)
references
References 99 publications
1
26
0
2
Order By: Relevance
“…However, no data were reported regarding its specificity and sensibility in detecting post-procedural cholangiocarcinoma residual cells. Further studies could be required to assess its potentiality as a post-LA evaluation device [43,44].…”
Section: Discussionmentioning
confidence: 99%
“…However, no data were reported regarding its specificity and sensibility in detecting post-procedural cholangiocarcinoma residual cells. Further studies could be required to assess its potentiality as a post-LA evaluation device [43,44].…”
Section: Discussionmentioning
confidence: 99%
“…Due to the advantages of this system, it was possible to ablate larger and more homogeneously tissue volumes and additionally the system is able to automatically stop the sonication if the temperature reaches a user-predefined threshold in order to prevent under-or overtreatment. 27 In a recently published review article, 27 44 studies reported on the clinical use of HIFU to treat liver lesions, while 19 series were found on HIFU treatment of pancreatic cancers and 4 included patients suffering from both liver and pancreatic cancers, reporting on a total of 1,682 and 823 cases for liver and pancreas, respectively. However, there is still no clear place in the algorithm of treatment of HCC as the availability of the modality is still limited.…”
Section: Irreversible Electroporationmentioning
confidence: 99%
“…Акустическую интенсивность постепенно увеличивают в области фокуса до тех пор, пока в зоне воздействия не будут определяться признаки коагуляционного некроза. После лечения пациенты требуют обязательного наблюдения в условиях стационара в течение нескольких дней [21,22].…”
Section: высокоинтенсивная фокусированная ультразвуковая терапияunclassified
“…Во время сеанса акустическая мощность воздействия подбирается в зависимости от уровня болевого порога пациента и корректируется в процессе процедуры с учетом его жалоб. Данные сеансы не ухудшают значительно субъективное самочувствие пациентов и не снижают их работоспособности, в связи с чем могут выполняться амбулаторно [21,22].…”
Section: высокоинтенсивная фокусированная ультразвуковая терапияunclassified